Comparison of mathematical problem posing skills of university students in the context of critical thinking dispositions - Arıkan, Elif Esra; Arıkan, Elif Esra (İstanbul Sabahattin Zaim Üniversitesi, Eğitim Fakültesi, 2019)
The purpose of this study is to question the existence of a relationship between the tendency to think critically and the ability to form mathematical problems. In other words, questioning the ability of mathematical problem-setting to be a sign of the existence of critical thinking. Participants of the research are 120 first-year university students of architecture faculty. In the study, the "if not" strategy was used for the mathematical problem-setting activity. Students are asked to solve this problem by giving an integral calculation problem, to create new problems from this problem and to solve the problems they have created. The problem chosen is one of the most fundamental integral problems in any analysis book. In addition, the California Critical Thinking Tendency Inventory was applied for all 120 learners. The corrational survey model was used in this study. One of the conclusions is that the subscale scores of the students who pose 3 or more types of problems are higher than the others.

Bu çalışmanın amacı, eleştirel düşünme eğilimi ve matematiksel problem kurma becerisi arasındaki ilişkinin varlığını sorgulamaktır. Başka bir deyişle, matematiksel problem kurma becerisinin eleştirel düşünme bağlamında sorgulamaktır. Bu çalışmada tarama modeli kullanılmıştır. Araştırmanın katılımcıları 120 kişiden oluşan mimarlık fakültesi birinci sınıf üniversite öğrencisidir. Çalışmada, matematiksel problem kurma aktivitesi için "eğer yoksa" stratejisi kullanılmıştır. Öğrencilere integral bir hesaplama problemi verilerek bu problemi çözmeleri, bu problemden yeni problemler oluşturmaları ve yine bu oluşturdukları problemleri çözmeleri istenmiştir. Seçilen problem herhangi bir analiz kitabında yer alan en temel integral problemlerden biridir. Ayrıca, 120 öğrencinin tamamı için California Eleştirel Düşünme Eğilimi Envanteri uygulanmıştır. Sonuçlardan biri verilen problemden yeni problem üreten öğrencileriden; sınırları değiştirme, fonksiyonu değiştirme, integrandı değiştirme ve isteneni değiştirme kategorilerinden üç ve üzeri sınıflamaya giren öğrencilerin eleştirel düşünme alt ölçek puanları diğerlerine nazaran daha yüksektir.
Eleştirel düşünme bağlamında üniversite öğrencilerinin matematiksel problem kurma becerilerinin karşılaştırılması
Keywords: Mathematical Problem Posing; What-if-not Strategy; Critical Thinking; Matematiksel problem kurma; What-if-not Stratejisi; Eleştirel Düşünme